Evaluation of learned helplessness, self-efficacy and disease activity, functional capacity and pain in Argentinian patients with rheumatoid arthritis. (2nd January 2017) - Vergara, F; Rosa, J; Orozco, C; Bertiller, E; Gallardo, MA; Bravo, M; Catay, E; Collado, V; Gómez, G; Sabelli, M; García, MV; Rosemffet, MG; et al.
Abstract : Objectives : To evaluate the association between learned helplessness (LH) and self-efficacy (SE) with disease activity, functional capacity, and level of pain in patients with rheumatoid arthritis (RA) and to compare LH and SE between patients in remission and patients with active disease. Method : This multicentre, cross-sectional study included consecutive patients (aged ≥ 18 years) with RA according to 2010 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) criteria. LH was measured by the Rheumatology Attitude Index (RAI), Spanish version; SE with the Arthritis Self-efficacy Scale (ASES), Spanish version; functional capacity with the Health Assessment Questionnaire, Argentinian version (HAQ-A); and perceived pain by the visual analogue scale (VAS). Disease activity was measured by the Clinical Disease Activity Index (CDAI). Results : A total of 115 patients (82% females) with a mean (± sd) age of 58 ± 13 years were included. We found a significantly positive correlation between LH and perceived pain (p < 0.001), HAQ-A score (p < 0.001), and CDAI (p < 0.001) and a significantly negative correlation between SE and perceived pain (p < 0.001), HAQ-A score (p < 0.001), and CDAI (p < 0.001). We found greater levels of SE and lower grades of LH in patients in remission compared to those with active disease (median 76 vs. 58; p < 0.001 and 6 vs. 11; p < 0.001, respectively). Conclusions : LH and SE correlated significantly with disease activity, functional capacity, and perceived pain. Levels of SE were higher in patients in remission compared to those with active disease as opposed to levels of LH, which were lower in patients in remission compared to those with active disease. These results show that cognitive factors are related to disease activity and their modifications may have importance in the management of RA.